Giorgina Levi in Bolivia (1939-1946). Mediations, Interactions and Emotions of en Exile - Perassi, Emilia (Oltreoceano - Rivista sulle migrazioni, 2024)
This contribution aims to address the exile experience and practices developed by Giorgina Levi during the seven years (1939 - 1946) of her stay in Bolivia. Her experience was recounted in the accurate volume edited by Marcella Filippa (Avrei capovolto le montagne, Giunti, Florence 1990), in which an organic palimpsest of letters and interviews with Giorgina allows us to listen to the first-person voice of the protagonist and observe her strategies of self-representation. Little studied, the text outlines the specific features of the transexilic topography traced by Georgina Levi: a topography whose lines are articulated in both the inter-American (Bolivia and Argentina) and trans-American (Bolivia and Italy) horizons. The intention is to traverse the stratified world of interactions, mediations and emotions constructed by the exile from the apparent solitude of the high Bolivian peaks. «If I had not been in Bolivia, I would not be the same», Giorgina wrote several times: a new relational identity proliferated from exile, which would remain a distinctive feature of Levi’s personality and political action after her return to Italy. An identity transformed or enriched by the variety of contacts she made with multiple social actors: from Bolivian miners to leading figures of the Latin American left or Jewish exiles she met along the way, with whom she built networks of friendship and social and political collaboration. Exile, from an experience of loss, is transformed into a «trump card» (Philippa 246), that is, into a productive and transformative experience.